Thoracic Paravertebral Block for Tube Thoracostomy Analgesia in the Emergency Department: A Case Report - M. Townsend Reeves (Clinical Practice and Cases in Emergency Medicine)
Introduction: Tube thoracostomy is a common yet exceedingly painful emergency department (ED) procedure, primarily used for pneumothorax evacuation. To facilitate safe performance, stable patients generally receive intravenous anxiolytic or opioid premedication, or perhaps even procedural sedation, in combination with local anesthetic infiltration of the insertion tract. However, more advanced pain management strategies, such as ultrasound-guided truncal blocks, offer a targeted and effective analgesic alternative without the risks or side effect profile inherent to sedation and opioid administration. Herein, a case is presented of painless ED tube thoracostomy following an ultrasound-guided thoracic paravertebral block (TPVB). Case Report: A 74-year-old female presented to the ED with chest pain and dyspnea from a recurrent, large right-sided spontaneous pneumothorax. An ultrasound-guided thoracic paravertebral block was performed for full-thickness chest wall analgesia prior to tube thoracostomy. A pigtail catheter was inserted painlessly into the pleural space without need for rescue analgesia or procedural sedation, and the pneumothorax was successfully evacuated. Conclusion: Ultrasound-guided regional anesthesia is increasingly employed in the emergency care setting as part of an opioid-sparing, multimodal analgesia strategy to manage acute pain. For chest tube insertion, the ultrasound-guided thoracic paravertebral block provides potent, long-lasting, and non-euphorigenic, hemithoracic analgesia across multiple contiguous dermatomes from skin to parietal pleura, reducing the need for procedural sedation and opioid therapy while avoiding the incomplete chest wall blockade often associated with other truncal blocks. It is a valuable addition to the analgesic armamentarium of the emergency physician, enabling more comprehensive pain control prior to tube thoracostomy.